Faecal virome transplantation decreases symptoms of type 2 diabetes and obesity in a murine model. Issue 12 (12th March 2020) - Rasmussen, Torben Sølbeck; Mentzel, Caroline Märta Junker; Kot, Witold; Castro-Mejía, Josué Leonardo; Zuffa, Simone; Swann, Jonathan Richard; Hansen, Lars Hestbjerg; Vogensen, Finn Kvist; Hansen, Axel Kornerup; Nielsen, Dennis Sandris
Abstract : Objective: Development of obesity and type 2 diabetes (T2D) are associated with gut microbiota (GM) changes. The gut viral community is predominated by bacteriophages (phages), which are viruses that attack bacteria in a host-specific manner. The antagonistic behaviour of phages has the potential to alter the GM. As a proof-of-concept, we demonstrate the efficacy of faecal virome transplantation (FVT) from lean donors for shifting the phenotype of obese mice into closer resemblance of lean mice. Design: The FVT consisted of viromes with distinct profiles extracted from the caecal content of mice from different vendors that were fed a low-fat (LF) diet for 14 weeks. Male C57BL/6NTac mice were divided into five groups: LF (as diet control), high-fat (HF) diet, HF+ampicillin (Amp), HF+Amp+FVT and HF+FVT. At weeks 6 and 7 of the study, the HF+FVT and HF+Amp+FVT mice were treated with FVT by oral gavage. The Amp groups were treated with Amp 24 hours prior to first FVT treatment. Results: Six weeks after first FVT, the HF+FVT mice showed a significant decrease in weight gain compared with the HF group. Further, glucose tolerance was comparable between the LF and HF+FVT mice, while the other HF groups all had impaired glucose tolerance. These observations were supported by significant shifts in GM composition, blood plasma metabolome and expression levels of genes associated with obesity and T2D development. Conclusions: Transfer of caecal viral communities from mice with a lean phenotype into mice with an obese phenotype led to reduced weight gain and normalised blood glucose parameters relative to lean mice. We hypothesise that this effect is mediated via FVT-induced GM changes.